Estimating the size of the potential market for the Kyoto flexibility machanisms - Zhong Xiang Zhang (Fondazione Eni Enrico Mattei (FEEM), 2000)
The Kyoto Protocol incorporates emissions trading, joint implementation and the clean development mechanism to help Annex I countries to meet their Kyoto targets at a lower overall cost. This paper aims to estimate the size of the potential market for all three flexibility mechanisms under the Kyoto Protocol over the first commitment period 2008-2012, both on the demand side and on the supply side. Based on the national communications from 35 Annex I countries, the paper first estimates the potential demand in the greenhouse gas offset market. Then, the paper provides a quantitative assessment of the implications of the EU proposal for concrete ceilings on the use of flexibility mechanisms for the division of abatement actions at home and abroad. Finally, using the 12-region's marginal abatement cost-based model, the paper estimates the contributions of three flexibility mechanisms to meet the total emissions reductions required of Annex I countries under the four trading scenarios respectively. Our results clearly demonstrate that the fewer the restrictions on trading the gains from trading are greater. The gains are unevenly distributed, however, with Annex I countries that have the highest autarkic marginal abatement costs tending to benefit the most. With respect to developing countries, their net gains are highest when trading in hot air is not allowed, and China and India account for about three-quarters of the total developing countries' exported permits to the Annex I regions.
Keywords: Q28; Q25; Q48; Q43; 330; Marginal abatement costs; emissions trading; clean development mechanism; joint implementation; Kyoto Protocol; greenhouse gases; European Union; hot air; CDM market; supplementarity restrictions; price of permits; Klimaschutz; Emissionshandel; Lizenz; Markt; Welt